PERBANDINGAN KEDUDUKAN ANAK ANGKAT DALAM PEROLEHAN HARTA WARIS BERDASARKAN HUKUM ISLAM DAN HUKUM PERDATA DALAM PUTUSAN PENGADILAN TINGGI BANGKA BELITUNG NOMOR 3/PDT/2012/PT.BABEL - Rayi Kharisma Rajib; Evani Fairuz Laylatul Sya’ban (Jurnal Riset Multidisiplin Edukasi, 2026)
This study is motivated by the fundamental differences between Islamic law and civil law in determining the legal status of adopted children, particularly in relation to inheritance rights, which often lead to legal uncertainty in society. This issue becomes more complex in judicial practice, as reflected in the Decision of the High Court of Bangka Belitung Number 3/PDT/2012/PT.BABEL. This research aims to analyze the position of adopted children from the perspectives of Islamic law and civil law and to compare their application in the उक्त decision. The method used is normative legal research with a statutory approach and a case approach, supported by primary, secondary, and tertiary legal materials, and analyzed qualitatively. The results show that Islamic law does not recognize adopted children as legal heirs but provides protection through the concept of obligatory bequest (wasiat wajibah), whereas civil law allows adopted children to obtain inheritance rights provided the adoption is legally valid. In the examined decision, the judges tend to prioritize substantive justice by considering the factual relationship between the adopted child and the adoptive parents. The implication of this study is the need for harmonization between the two legal systems to achieve greater legal certainty and justice in resolving inheritance disputes involving adopted children.